2011
DOI: 10.3390/ijerph8083380
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Epidemiology into Dichloromethane and Cancer Risk

Abstract: Dichloromethane (methylene chloride) is a widely used chlorinated solvent. We review the available epidemiology studies (five cohort studies, 13 case-control studies, including seven of hematopoietic cancers), focusing on specific cancer sites. There was little indication of an increased risk of lung cancer in the cohort studies (standardized mortality ratios ranging from 0.46 to 1.21). These cohorts are relatively small, and variable effects (e.g., point estimates ranging from 0.5 to 2.0) were seen for the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…Previous studies have not indicated an excess risk of lung cancer associated with exposure to TCE and methylene chloride 6 7 41. For methylene chloride, our results showed a null association both overall and across the various subgroup analyses.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies have not indicated an excess risk of lung cancer associated with exposure to TCE and methylene chloride 6 7 41. For methylene chloride, our results showed a null association both overall and across the various subgroup analyses.…”
Section: Discussioncontrasting
confidence: 69%
“…This study demonstrated the hepatotoxic effects of acute inhalation exposure to 1,2‐DCP, DCM and their combination and preliminarily clarified the relative mechanism of 1,2‐DCP and DCM‐induced liver damage. The changes in liver weight, elevated serum transaminase and pathological changes in the liver suggest that 1,2‐DCP produces hepatocellular necrosis and liver damage in mice, and our results are in agreement with previous reports (Cooper, Scott, & Bale, ; Gi et al, 2015b; Yanagiba et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Lymphoma has been ranked as one of the top ten malignant tumors in this century, and it has the fastest growing incidence rate of all malignant tumors in China [27]. Despite the inherent biases, certain chemical pollutants should be carefully considered [28,29]. Germ cell tumors are also thought to be closely related to environmental factors.…”
Section: Discussionmentioning
confidence: 99%